Social preferences and political attitudes: An online experiment on a large heterogeneous sample - Rudolf Kerschbamer; Daniel Muller (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2017)
This paper investigates - in a large heterogeneous sample - the relationship between social preferences on the one hand, and socioeconomic factors and political preferences on the other hand. Socioeconomic factors correlate with social preferences, and social preferences robustly shape political attitudes and voting behavior in a particular way: Selfish subjects are the extremists on one side of the political spectrum - they are more likely to vote for a rightwing party, they are less inclined to favor redistribution and they are more likely to self-assess themselves as right-wing than all the other types. Inequality-averse subjects, altruists and maxi-min sit at the opposite end of the political spectrum, while all the other types behave less systematically and in a less extreme fashion. Overall, our evidence indicates that elicited social preferences are externally valid as a predictor for political attitudes, and that social preferences are fairly stable across contexts and over longer periods of time.
Keywords: C91; D30; D63; D64; D72; H50; 330; Distributional Preferences; Social Preferences; Equality Equivalence Test; Political Attitudes; Voting Behavior; German Internet Panel